INNOVATIVE TOOLKIT FOR FORMING AN EPS PORTFOLIO FOR ELECTRONIC TRADING PLATFORMS - Volvach, Olena (Socio-economic relations in the digital society, 2023)
When companies enter the e-commerce market, choosing an electronic payment system that fits well with the way they do business is relevant and one of the main concerns. Realizing this, almost all stakeholders are studying the different types of electronic payment systems and the challenges associated with electronic payment systems and digital currency. This study is aimed at outlining innovative tools for forming a portfolio of electronic payment systems for modern trading platforms in the e-commerce market. Achieving this goal involves solving a number of tasks, in particular highlighting the features of the application of electronic payment systems and the criteria that form the basis of the formation of an effective electronic payment systems (EPS) portfolio. Within the framework of this study, multi-criteria optimization using fuzzy logic methods was applied as a decision-making method to help trading platforms make decisions regarding the evaluation of EPS efficiency and the formation and management of a portfolio of electronic payment systems among a wide range of possible options. The research results demonstrate the high effectiveness of fuzzy logic methods, in particular Fuzzy TOPSIS, to achieve the research goal. The conclusions and recommendations formed will be useful both from a theoretical and a practical point of view for representatives of e-commerce and the scientific society in order to develop the methodology for managing electronic payment systems.
Keywords: electronic commerce; portfolio strategy; electronic trading platform; electronic payment system; innovations; unclear logic; mathematical model; fuzzy TOPSIS